2009
DOI: 10.1177/1553350609334821
|View full text |Cite
|
Sign up to set email alerts
|

Does Negative Pressure Wound Therapy Have a Role in Preventing Poststernotomy Wound Complications?

Abstract: In this high-risk cohort, 3 postoperative SWI cases were anticipated but may have been mitigated by NPWT. This is an easily applied and well-tolerated therapy and may stimulate more effective wound healing. Among patients with increased SWI risk, strong consideration should be given to NPWT as a form of "well wound" therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
133
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(140 citation statements)
references
References 37 publications
2
133
1
4
Order By: Relevance
“…The effect of iNPWT on wound exudate might be explained by the known biomechanical mechanisms that iNPWT applies to the tissue, such as a reduction in oedema, increased blood flow14, 19 and lymph clearance21. In contrast to the study on wound exudate (S. Karlakki et al ., personal communication), the study that investigated ‘days to dry wounds’33 as a primary outcome found no effect of iNPWT.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The effect of iNPWT on wound exudate might be explained by the known biomechanical mechanisms that iNPWT applies to the tissue, such as a reduction in oedema, increased blood flow14, 19 and lymph clearance21. In contrast to the study on wound exudate (S. Karlakki et al ., personal communication), the study that investigated ‘days to dry wounds’33 as a primary outcome found no effect of iNPWT.…”
Section: Discussionmentioning
confidence: 91%
“…In the latter case, the liquid is removed by evaporation through a semipermeable dressing. The mechanisms of action of this closed incision management have been supported by biomechanical studies: increased blood flow14, 19; decreased lateral and shear stress at the suture lines with decreased risk of wound dehiscence20; and increased lymph clearance with reduced formation of haematoma/seroma21 ( Fig . 1).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Grauhan et al [111] showed significant reduction of SSIs in obese patients (body mass index > 30 kg/m 2 ) with median sternotomy compared with patients treated with standard wound dressings. In general, retrospective studies and randomized controlled trials provided a substantial body of evidence that the use of this prophylactic wound dressing technique may reduce the incidence of wound infections [112][113][114] . …”
mentioning
confidence: 99%
“…However a more recent randomized controlled trial evaluating the impact of gentamicin-soaked collagen sponge on poststernotomy wound infection did not show a n a d v a n t a g e o f t h i s a p p r o a c h o v e r controls [116]. Based on the aforementioned successes with NPT in the treatment of documented DSWI we and others have recently evaluated the application of NPT to clean, closed incisions as a method to prevent complications in high-risk wounds [117,118]. We initially applied this form of "well wound therapy" in a cohort of 57 adult cardiac surgery patients known to be at increased risk for DSWI based on a validated risk stratification model [13].…”
Section: Can Mediastinitis Be Prevented?mentioning
confidence: 99%